Hybrid Warfare Security and Asymmetric Conflict in International Relations - Weissmann, Mikael; Nilsson, Niklas; Palmertz, Björn; Thunholm, Per (Bloomsbury Academic, 2021)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Hybrid Warfare refers to a military strategy that blends conventional warfare, so-called 'irregular warfare' and cyber-attacks with other influencing methods, such as fake news, diplomacy and foreign political intervention. As Hybrid Warfare becomes increasingly commonplace, there is an imminent need for research bringing attention to how these challenges can be addressed in order to develop a comprehensive approach towards Hybrid Threats and Hybrid Warfare. This volume supports the development of such an approach by bringing together practitioners and scholarly perspectives on the topic and by covering the threats themselves, as well as the tools and means to counter them, together with a number of real-world case studies. The book covers numerous aspects of current Hybrid Warfare discourses including a discussion of the perspectives of key western actors such as NATO, the US and the EU; an analysis of Russia and China's Hybrid Warfare capabilities; and the growing threat of cyberwarfare. A range of global case studies - featuring specific examples from the Baltics, Taiwan, Ukraine, Iran and Catalonia - are drawn upon to demonstrate the employment of Hybrid Warfare tactics and how they have been countered in practice. Finally, the editors propose a new method through which to understand the dynamics of Hybrid Threats, Warfare and their countermeasures, termed the 'Hybridity Blizzard Model'. With a focus on practitioner insight and practicable International Relations theory, this volume is an essential guide to identifying, analysing and countering Hybrid Threats and Warfare.